Comparative Factors Influencing Consumer Interest in Purchasing Second-Hand Goods in Japan and Indonesia - Fajar Mudzoffar Addya; Citra Savitri; Dedy mulyadi; Budi Rismayadi; Lee Bun (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The second-hand product trade is rapidly growing in today’s global era, both in physical markets and digital platforms. Used goods serve as an alternative to meet primary and secondary needs, particularly among lower-middle-income communities, although they are also increasingly favored by higher income groups. This study aims to compare consumer purchase interest in second-hand goods between Indonesia and Japan. A descriptive qualitative method with a case study approach was used, involving consumers from both countries. The findings show a high interest in used goods, with the number of buyers exceeding that of sellers. However, challenges such as inaccurate product information and quality mismatches persist in the buying process. Overall, purchase interest in Japan is higher than in Indonesia, supported by more advanced digital platforms. These findings indicate that second-hand products hold significant market potential in both developing and developed countries.